Terrorism and the state : rethinking the rules of state responsibility - Becker, Tal (Hart monographs in transnational and international law., 2006)
Analyses the legal principles that govern State responsibility for the conduct of non-State actors, and examines their relevance and effectiveness in an interconnected world. This book argues that traditional approaches to determining the State's legal responsibility for violations of the counter-terrorism obligations lack conceptual coherence.